Linking primatology and archaeology: the transversality of stone percussive behaviors. - (:unkn) unknown (My University, 2023)
Since the launch of the Journal of Human Evolution fifty years ago, the archaeology of human origins and the evolution of culture have witnessed major breakthroughs with the identification of several new archaeological sites whose chronology has been slowly pushed back until the discovery of the earliest evidence of stone tool making at Lomekwi 3 (West Turkana, Kenya), at 3.3 Ma. Parallel to these dis- coveries, the study of wild primates, especially chimpanzees (Pan troglodytes), allowed the development of models to understand key aspects of the behavior of extinct hominin species. Indeed, chimpanzees possess an impressive diversity of tool-aided foraging behaviors, demonstrating that technology (and culture) is not exclusive to humans. Additionally, current research has also shown that wild capuchin monkeys (Sapajus libidinosus) and long-tailed macaques (Macaca fascicularis) also rely on stone percussive foraging behaviors. The investigation of these primates is boosting new interpretative models to understand the origins of stone flaking and the archaeological signature left by these primates. This review aims to present an examination of the state-of-the-art and the current advances made in the study of the earliest hominin technology and primate percussive behaviors. Overall, we argue that while it has been shown that extant primates can generate unintentional flakes, early hominins exhibited skills in the production and use of flakes not identified in primates. Nonetheless, we stand up to continue developing interdisciplinary approaches (i.e., primate archaeology) to study extant primates, as these endeavors are essential to move forward toward a detailed understanding of the technological foraging behaviors beyond the genus Homo. Finally, we discuss future challenges for the study of the emergence of stone technology.
Keywords: African Research